Effective removal of furfural by ultraviolet activated persulfate, peroxide, and percarbonate oxidation: Focus on influencing factors, kinetics, and water matrix effect - Can-Guven, Emine; Daniser, Yesim; Guvenc, Senem Yazici; Ghanbari, Farshid; Varank, Gamze (ELSEVIER SCIENCE SA, 2022)
In this study, the degradation of furfural by ultraviolet (UV) based advanced oxidation processes was investigated. The oxidation performance of percarbonate (PC), an alternative oxidant to hydrogen peroxide was evaluated with hydrogen peroxide (HP) and persulfate (PS) oxidation processes. UV was applied to activate oxidants and the effect of process variables (initial pH, oxidant dose, initial pollutant concentration) on furfural removal from aqueous solution was investigated. The optimum pH value was determined as 5 in the three processes. The optimum oxidant dose was determined as 5 mM in UV/HP and UV/PC processes, and 2.5 mM in the UV/PS process. Furfural removal efficiencies by UV/PS, UV/HP, and UV/PC processes were 94.7 %, 83.1 %, and 90.1 %, respectively at 25 mg/L initial furfural concentration. The pseudo-first-order reaction kinetic model was applied to determine the reaction kinetics in furfural degradation, and it was determined that UV-based advanced oxidation processes and furfural removal fit the first-order kinetic model with a high coefficient of determination values. The results showed that the removal efficiencies and reaction rate is directly proportional to the oxidant dose and inversely proportional to the initial furfural concentration. The effect of the water matrix on the furfural removal efficiency of the three processes was also investigated. The carbonate, bicarbonate, chloride, nitrate, and phosphate anions in the water decreased the removal efficiency at different rates, and this decrease was more pronounced in UV/HP and UV/PC processes. EE/O values calculated for UV/PS, UV/HP, and UV/PC processes were 20.90, 34.54, and 26.55 kWh/m3/order, respectively.
Keywords: Carbonate; Electrical energy per order; Peroxide; Persulfate; Ultraviolet; HYDROGEN-PEROXIDE; SODIUM PERCARBONATE; AQUEOUS-SOLUTION; DEGRADATION; ADSORPTION; CARBON; PEROXYMONOSULFATE; BENZENE; UV; MECHANISM; Chemistry